Finance, development, and the IMF - Boughton, James M.; Lombardi, Domenico (Oxford : Oxford University Press, 2009)
An interdisciplinary collection of essays from leading academics and experts addressing how the IMF can support economic growth, poverty reduction, and macroeconomic stability in the world's poorest regions.
Description based on print version record.
Includes bibliographical references and index.
Keywords: International Monetary Fund; Economic development; Economic assistance